Mutational mechanisms shaping the coding and noncoding genome of germinal center derived B-cell lymphomas - Hübschmann, Daniel; Kleinheinz, Kortine; Wagener, Rabea; Bernhart, Stephan H.; López, Cristina; Toprak, Umut; Sungalee, Stéphanie; Ishaque, Naveed; Kretzmer, Helene; Kreuz, Markus; Waszak, Sebastian Martin; Paramasivam, Nagarajan; et al. (Leukemia, 2021)
B cells have the unique property to somatically alter their immunoglobulin (IG) genes by V(D)J recombination, somatic hypermutation (SHM) and class-switch recombination (CSR). Aberrant targeting of these mechanisms is implicated in lymphomagenesis, but the mutational processes are poorly understood. By performing whole genome and transcriptome sequencing of 181 germinal center derived B-cell lymphomas (gcBCL) we identified distinct mutational signatures linked to SHM and CSR. We show that not only SHM, but presumably also CSR causes off-target mutations in non-IG genes. Kataegis clusters with high mutational density mainly affected early replicating regions and were enriched for SHM- and CSR-mediated off-target mutations. Moreover, they often co-occurred in loci physically interacting in the nucleus, suggesting that mutation hotspots promote increased mutation targeting of spatially co-localized loci (termed hypermutation by proxy). Only around 1% of somatic small variants were in protein coding sequences, but in about half of the driver genes, a contribution of B-cell specific mutational processes to their mutations was found. The B-cell-specific mutational processes contribute to both lymphoma initiation and intratumoral heterogeneity. Overall, we demonstrate that mutational processes involved in the development of gcBCL are more complex than previously appreciated, and that B cell-specific mutational processes contribute via diverse mechanisms to lymphomagenesis.
Affiliations: Daniel Hübschmann, Kortine Kleinheinz, Rabea Wagener, Stephan H. Bernhart, Cristina López, Umut H. Toprak, Stephanie Sungalee, Naveed Ishaque, Helene Kretzmer, Markus Kreuz, Sebastian M. Waszak, Nagarajan Paramasivam, Ole Ammerpohl, Sietse M. Aukema, Renée Beekman, Anke K. Bergmann, Matthias Bieg, Hans Binder, Arndt Borkhardt, Christoph Borst, Benedikt Brors, Philipp Bruns, Enrique Carrillo de Santa Pau, Alexander Claviez, Gero Doose, Andrea Haake, Dennis Karsch, Siegfried Haas, Martin-Leo Hansmann, Jessica I. Hoell, Volker Hovestadt, Bingding Huang, Michael Hummel, Christina Jäger-Schmidt, Jules N.A. Kerssemakers, Jan O. Korbel, Dieter Kube, Chris Lawerenz, Dido Lenze, Joost H.A. Martens, German Ott, Bernhard Radlwimmer, Eva Reisinger, Julia Richter, Daniel Rico, Philip Rosenstiel, Andreas Rosenwald, Markus Schillhabel, Stephan Stilgenbauer, Peter F. Stadler, José I. Martín-Subero, Monika Szczepanowski, Gregor Warsow, Marc A. Weniger, Marc Zapatka, Alfonso Valencia, Hendrik G. Stunnenberg, Peter Lichter, Peter Möller, Markus Loeffler, Roland Eils, Wolfram Klapper, Steve Hoffmann, Lorenz Trümper, ICGC MMML-Seq consortium, ICGC DE-Mining consortium, BLUEPRINT consortium, Ralf Küppers, Matthias Schlesner, Reiner Siebert
Gesehen am 03.02.2022